Eothenomys lemminus Miller 1899 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Eothenomys lemminus Miller, 1899. Proc. Acad. Nat. Sci. Phila., (1898), p. 369. TYPE LOCALITY: U.S. S. R., R.S.F.S. R., Khabarovsk. Krai, Chukotsk. Nat. Okr., Zaliv Sv. Kresta, S.W. of Egvekinom, "Kelsey Station, Plover Bay, Bering Strait". DISTRIBUTION: Chukotka Peninsula (N. E. Siberia), west to Lena River and south to Amur River (U.S. S.R.). COMMENT: Formerly included in Aschizomys; see comments under Eothenomys. Most Russian authors have allocated this species to the genus Alticola, usually as a subspecies of A. macrotis; see Yudin et al., 1976, [Small mammals of the northern Far East,] Nauka Sibir. Otd. Novosibirsk, 270 pp., Gromov and Polyakov, 1977:133, and Gromov and Baranova, 1981: 177. Corbet, 1978:100, provisionally placed it in Eothenomys, calling it an "enigmatic species"; Aimi, 1980, Mem. Fac. Sci. Kyoto Univ. Ser. Biol., 8:35-84, provided additional evidence for this allocation, which is followed here. Bykova et al., 1978, Experientia, 34: 1146-1148, suggested that there may be more than one Siberian species. ISIS NUMBER: 5301410008070001001 as Aschizomys lemminus. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 4), pp. 477-504 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 486, DOI: 10.5281/zenodo.7353034